Draft 8th Five Year Plan 1990-95 and Annual Plan 1991-92 Government of Mizoram - Planning Commission (Planning Commission, 1990)
Mizoram occupies a very strategic position in the North Eastern corner of India having an International boundary of 710 Kms and covers an area of 21,081 Sq. Kms. The Tropic of Cancer runs through the State of Mizoram. It is bounded on the North by the States of Assam and Manipur, on the East and South by Chin Hills of Burma and on the West by Chittagong Hill Tracts in Bangladesh and the State of Tripura. It is linked with the State of Assam on the. North of the State the hill areas of Mizoram enjoy cool temperate climate. The average annual rainfall is 217.5 C.M. The temperature varies between 12° Centigrade to 18° Centigrate.in Winter and 18° Centigrade to 29 Centigrade in summer.
Government of Mizoram
Planning & Programme Implementations Department Mizoram
Keywords: Crop Husbandry including Agriculture Research & Education; Food; Storage; Water housing & Marketing; Land Reforms; Forest & Wild Life; Economics & Statistics; Civil Supplies; Weights & Measures; District Councils; Higher & Technical Education; Sports & Youth Services; Motor Vehicle Wing; Local Administration; State Capital Project